Les fonts clàssiques de Curial e Güelfa. - SOLER, ABEL (Scripta)
Curial e Güelfa (Milan-Naples, ca. 1445-1448), a chivalric romance written in Catalan an attributable to the great chamberlain in the Naples of Alfonso the Magnanimous, Enyego/Inico d'Àvalos, contains a suggestive cultural burden (Ovid's myths satirically distorted; theophanies and Neo-platonic sets; explicit and/or implicit references to Caesar, Macrobius, Plato, Apuleius...), which is not absolutely superfluous nor dispensable, as some critic from the last century explained. Just the opposite: the way to recall the classics and re-present them cannot be explained without considering the contacts of the hypothetical writer with the Lombard and Neapolitan Humanism. On the other hand, the catalogue of Greek-Latin classics recorded in the varied personal library of D'Àvalos himself, the second richest in the south of Italy, demonstrates the coincidence of his taste and readings with the anonymous writer of the Curial and invites us to ratify the aforementioned attribution.